2017
DOI: 10.1097/md.0000000000007434
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of autograft and allograft tendons in posterior cruciate ligament reconstruction

Abstract: Background:The purpose of this meta-analysis of randomized controlled trials (RCTs) and non-RCTs was to compare the clinical outcomes of autograft versus allograft tendons in patients who underwent posterior cruciate ligament (PCL) reconstruction.Methods:We conducted a search of PubMed, EMBASE, The Cochrane Library, and Web of Science databases for RCTs and non-RCTs comparing autograft and allograft tendons in PCL reconstruction up to August 2016. The outcomes were Lysholm knee function score, postoperative ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Tian et al [ 22 ] provide a meta-analysis of autograft and allografts in PCL reconstruction but include only five studies, the RCT by Li et al [ 12 ], and CCTs by Ahn et al [ 1 ], Li et al [ 11 ], Sun et al [ 21 ] and Wang et al [ 23 ], some of which we would exclude. Ahn et al [ 1 ] had only 18 patients in each group.…”
Section: Resultsmentioning
confidence: 99%
“…Tian et al [ 22 ] provide a meta-analysis of autograft and allografts in PCL reconstruction but include only five studies, the RCT by Li et al [ 12 ], and CCTs by Ahn et al [ 1 ], Li et al [ 11 ], Sun et al [ 21 ] and Wang et al [ 23 ], some of which we would exclude. Ahn et al [ 1 ] had only 18 patients in each group.…”
Section: Resultsmentioning
confidence: 99%
“…The aforementioned study published by Wang et al [14] in 2017 indicated that the average Lysholm score and Tegner activity score in an autogenous semitendinosus group were 86.2 and 7.68, respectively, whereas those in a hypothermia allogeneic tendon group were 85.0 and 7.74, respectively. A meta-analysis conducted by Tian et al [18] in 2017 demonstrated that the average Lysholm score and Tegner activity score in an autograft group were 82-87.8 and 4.7-7.7, respectively, whereas those in an allograft group were 84-92.3 and 4.7-7.1, respectively. A systematic review conducted by Lee et al [19] in 2018 revealed no statistically significant differences in the clinical results regardless of graft sources.…”
Section: Discussionmentioning
confidence: 99%
“…34 Some reviews reported no significant differences in postoperative functional outcomes using autografts compared to allografts, 14,15 whereas another metaanalysis reported insufficient evidence to report the superiority of allografts over autografts due to poor quality and data availability. 27,28 This review distinguishes the safety outcomes of PCL reconstruction from the effectiveness outcomes and suggests that there is insufficient evidence to judge superiority or inferiority of a particular graft type. It emphasizes poorly measured and reported complications because none of the primary studies reported on graft failure rates or revision or rerupture rates despite the reported graft failure rates of 11.6% and 12.6% mentioned in other studies.…”
Section: Discussionmentioning
confidence: 99%